Characteristic features of exact solutions of the problem of an electron in the quantized field of a plane wave; Soviet Physics Journal; Vol. 20, iss. 3 - Bagrov V. G. Vladislav Gavriilovich; Gitman D. M. Dmitry Maksimovich; Zadorozhnyi V. N. Valery Nikolaevich; Lavrov P. M. Peter Mikhailovich (1977, 1977)
Title screen